The Influence of the Children's Learning in Science (CLIS) Model on Student Motivation and Learning Outcomes in Integrated Thematic Learning - Putri, Eliza Nola Dwi; Miaz, Yalvema; Arief, Darnis; Neviyarni (Universitas Pendidikan Ganesha, 2025)
This research is motivated by students who have difficulty understanding learning concepts because the material discussed requires high memory, knowledge, and understanding skills, resulting in low learning motivation. This study aims to determine the effect of the CLIS learning model on student motivation and learning outcomes. The research method used is quantitative with a quasi-experimental design in the form of a pretest-posttest control group design. The research subjects consisted of 24 students in the experimental class and 24 students in the control class. Data collection was carried out through a learning motivation questionnaire and student achievement tests. Data were analyzed by calculating the scores obtained from each aspect of the questionnaire and hypothesis testing (t-test). The results of the study showed that first, there was an effect of CLIS on student learning motivation. Second, there was an effect of the CLIS model on student learning outcomes. Third, there was a high relationship between learning motivation and student learning outcomes. This study shows that the application of the CLIS learning model has a positive impact on student motivation and learning outcomes. The implications of these findings are very significant in the context of education, especially at the elementary level.